Ventricular Tachycardia Possibly Originated From the His‐Purkinje System May Result From Aconitine Poisoning - Honglin Ni; Changlin Zhai; Haihua Pan (Annals of Noninvasive Electrocardiology)
ABSTRACT Accurate diagnosis of wide QRS complex tachycardia (WCT) with the earliest ventricular origin potentially located in the His‐Purkinje system, and exploration of its etiology are helpful for further diagnosis and treatment. This article finds through specific cases that one of the possible etiologies is aconitine poisoning.